Medicolegal Implications of Nosocomial Infections: A Case Report of Aspergillus Contamination during Cardiac Surgery. Issue 3 (23rd December 2016) - Tuchtan, Lucile; Piercecchi‐Marti, Marie‐Dominique; Dumon, Henri; Métras, Dominique; Léonetti, Georges; Bartoli, Christophe
Abstract: Nosocomial infections have become a major issue of public health and lead to an increasing number of suits for damages. We present a rare case of Aspergillus contamination during cardiac surgery, describe the medicolegal investigation, and present the new system for compensation of bodily injury after nosocomial infection in France, based on the law of March 4, 2002 on patient rights and quality in the health system. This case demonstrates the limits of compensation for nosocomial infections on the grounds of national solidarity. The expert report requested by the regional commission for conciliation and compensation is of fundamental importance in enabling the commission to decide between fault and inherent risk of treatment.